2014
DOI: 10.3892/ol.2014.1972
|View full text |Cite
|
Sign up to set email alerts
|

Casticin inhibits self-renewal of liver cancer stem cells from the MHCC97 cell line

Abstract: Casticin exerts anticarcinogenic activity in several types of cancers, including human hepatocellular carcinoma (HCC). The aim of the present study was to investigate the effects of casticin, which is derived from Fructus Viticis Simplicifoliae, on the self-renewal capacity of liver cancer stem cells (LCSCs) derived from the HCC MHCC97 cell line. The present study demonstrated that casticin significantly inhibited the proliferation of LCSCs from the MHCC97 cell line in a dose-dependent manner (P<0.05), the hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…He et al (22) found that casticin inhibited epithelialmesenchymal transition (EMT) in liver cancer stem cells from the SMMC-7721 cell line by downregulating Twist. He et al (23) demonstrated casticin also suppressed self-renewal ability in liver cancer stem cells from the MHCC97 cell line. Our previous study showed that casticin suppressed the self-renewal and invasion abilities of LCSLCs from NSCLC A549 cells through p-Akt downregulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…He et al (22) found that casticin inhibited epithelialmesenchymal transition (EMT) in liver cancer stem cells from the SMMC-7721 cell line by downregulating Twist. He et al (23) demonstrated casticin also suppressed self-renewal ability in liver cancer stem cells from the MHCC97 cell line. Our previous study showed that casticin suppressed the self-renewal and invasion abilities of LCSLCs from NSCLC A549 cells through p-Akt downregulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Casticin, an anti-inflammatory molecule (32), inhibits numerous cancer cells (27,28,33). Previous studies demonstrated that casticin inhibited EMT in liver cancer stem cells (28) and induced apoptosis in ovarian cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Casticin, a biologically active component of Fructus viticis (20), possesses numerous biological and pharmacological effects, including immunomodulatory, anti-hyperprolactinemia, neuroprotective and anti-inflammatory properties (22)(23)(24)(25), and alters tumorigenesis and tumor progression (26,27). Additionally, it has been demonstrated that casticin suppresses EMT in hepatocellular carcinoma (28).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out on the effect of casticin on liver cancer stem cells (LCSCs) derived from the HCC cell cline. One such study conducted on the MHCC97 cell line found that casticin (IC50 value: 17.9 µM and 0.5 µM for parental cells and LCSCs, respectively) inhibited proliferative properties in a dose-dependent matter through the downregulation of B-catenin and blocking the Wnt/β-catenin pathway; the pathway regulates stem cell self-renewal and is present in liver cancer [76]. Another study evidenced the ability of casticin to induce apoptosis and G2/M cell cycle arrest in HepG2 and PLC/PRF/5 cells.…”
Section: Casticin and Hepatocellular Carcinomamentioning
confidence: 99%